Modal parameter identification of a spectator–grandstand interaction model under different rhythmic activities. Issue 9 (July 2019) - Naranjo-Pérez, Javier; Jiménez-Alonso, Javier Fernando; García-Sanchez, Felipe; Sáez, Andres
Stadium grandstands are designed to support high dynamic loads due to the presence of spectators attending both sport and music events. In order to assess accurately the dynamic response of these structures under these actions, spectator–grandstand interaction models have been widely considered. In spite of the wide range of different rhythmic activities, which can be performed by spectators on stadium grandstands, the modal parameters of these interaction models have been determined experimentally for only two extreme situations, the so-called passive and active spectators. In order to overcome this limitation, the variation of the modal parameters of a spectator–grandstand interaction model in terms of the rhythmic activities performed by the spectators was analyzed in this study. As parameters estimator, the ordinary least squares method was considered. The parameters identification has been performed based on the results of a full-scale experimental test conducted on a real grandstand. As result of the identification process, a clear variation of the modal parameters of the interaction model in terms of the activity type and rate has been detected. Therefore, this interaction model becomes a valuable tool for estimating the change on the modal properties of grandstands induced by the different rhythmic activities performed by the spectators.